KUALITAS PRODUK MEMPENGARUHI KEPUTUSAN PEMBELIAN IPHONE DI TAROGONG KALER KAB. GARUT - Moh Rizky Nugraha; Ramayani Yusuf; Wufron Wufron (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2024)
The growth of technology is in line with the times, the use of sophisticated communication tools is increasing. Smartphones have become a very useful communication tool used in activities and have become a means of supporting community activities. Product quality has an important role for the company and is the main thing in developing a product. Consumers make purchasing decisions after going through varios stages before deciding to make a purchase. The purpose of this research study is to find out what factors are related to product. The sampling technique distributed questionnaires to 100 respondents in the Tarogong Kaler area, Kab. Garut. Secondary data was obtained from previous research submitted by experts in the form of journal references, expert theories and library expert book references. Primary data comes from the result of a questionnaire sent to 100 respondents who have purchased IPhone smartphone products. The results of this research also state that IPhone products have good quality, therefore consumers are interested in IPhone products.